1989
DOI: 10.1002/jcp.1041410328
|View full text |Cite
|
Sign up to set email alerts
|

Agarose‐selected variants of two human tumor cell lines exhibit altered methionine auxotrophy

Abstract: Our aim was to determine if the selection of human tumor cells with enhanced anchorage-independent growth capacity was associated with alterations in methionine auxotrophy. Cells with an increased ability to form colonies on soft agarose were selected from human melanoma (MeWo) and neuroepithelioma (SK-N-MC) cell lines. In contrast to their respective parental lines, a high proportion of the agarose-selected variants were completely unable to proliferate in methionine-free medium containing its immediate precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…Methionine synthase activity in melanoma variants Previous results from our laboratory revealed that highly metastatic or anchorage-independent variants of the MeWo human melanoma tumor line were unable to proliferate in methionine-free Hcy-supplemented culture medium, in contrast to the parental MeWo line, which was able to grow under such conditions (Liteplo, 1989;Liteplo and Hipwell, 1989). Since the inability of these HcynRsP variants to proliferate or survive under such conditions appeared to be due to a defect in the in vivo synthesis of methionine from Hcy and 5-methyltetrahydrofolic acid, we examined in vitro methionine synthase activity in cell extracts prepared from MeWo, MeWo-LC1, and D3.12-2 cells.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Methionine synthase activity in melanoma variants Previous results from our laboratory revealed that highly metastatic or anchorage-independent variants of the MeWo human melanoma tumor line were unable to proliferate in methionine-free Hcy-supplemented culture medium, in contrast to the parental MeWo line, which was able to grow under such conditions (Liteplo, 1989;Liteplo and Hipwell, 1989). Since the inability of these HcynRsP variants to proliferate or survive under such conditions appeared to be due to a defect in the in vivo synthesis of methionine from Hcy and 5-methyltetrahydrofolic acid, we examined in vitro methionine synthase activity in cell extracts prepared from MeWo, MeWo-LC1, and D3.12-2 cells.…”
Section: Resultsmentioning
confidence: 96%
“…The ability of cells to proliferate in either Met+-or Hcy +-medium was routinely determined by measuring the incorporation of [meth~l-~HIthymidine into cellular DNA of cells grown for 5 days in the appropriate medium (Liteplo and Hipwell, 1989;Liteplo, 1989). Similar results were obtained when the cells were counted (Liteplo, 1989).…”
Section: Assay Of Hcy-dependent Growthmentioning
confidence: 98%
See 3 more Smart Citations